CircCCT2/miR-146a-5p/IRAK1 axis promotes the development of head and neck squamous cell carcinoma - Long He; Lanruo Li; Liting Zhao; Xiaoya Guan; Yujia Guo; Qi Han; Huina Guo; Hongliang Liu; Chunming Zhang (BMC Cancer)
Abstract Background Head and neck squamous cell carcinoma (HNSCC), a highly invasive malignancy with a poor prognosis, is one of the most common cancers globally. Circular RNAs (circRNAs) have become key regulators of human malignancies, but further studies are necessary to fully understand their functions and possible causes in HNSCC. Methods CircCCT2 expression levels in HNSCC tissues and cells were measured via qPCR. CircCCT2 was characterized by Sanger sequencing, qRT-PCR, RNase R & Actinomycin D treatment, nucleoplasmic separation and FISH experiments. CCK-8 and colony formation assays were performed to determine cell proliferation, and Transwell assays were used to determine migration and invasion. A xenograft tumor model was used to study the influence of circCCT2 on HNSCC in vivo. Dual-luciferase gene reporter, RIP, western blotting, and rescue experiments, were used to explore target-binding relationships and regulatory mechanisms. Results CircCCT2 was significantly upregulated in HNSCC tissues and cells. High circCCT2 levels were associated with advanced T stage, N stage, clinical stage and poor prognosis. Functionally, we verified that circCCT2 promotes HNSCC development in vitro and in vivo. Mechanistically, functioning as a competitive endogenous RNA (ceRNA) or miRNA sponge, circCCT2 binds directly to miR-146a-5p and increases interleukin-1 receptor-associated kinase 1 (IRAK1) levels, which enhances the malignant development of HNSCC by driving epithelial-mesenchymal transition (EMT). Conclusion CircCCT2 promotes HNSCC development through the miR-146a-5p/IRAK1 axis, revealing that circCCT2 is a potential biomarker and target for HNSCC.